1997
DOI: 10.1111/j.1439-0442.1997.tb01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Starch Digestion in The Horse

Abstract: Summary Structure of starch in feed and chyme of horses (7 with a cannula at the caudal end of the jejunum and 2 with a cecal fistula) after feeding high starch diets (maize: whole, broken, ground, expanded and as silage, oats: whole, rolled or ground, rolled barley, raw potatoes, and tapioca) was investigated by light and electron microscopy. Structure of feed starch and morphology or starch degradation in the chyme corresponded to data on preileal starch digestibility which was investigated in a parallel stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 9 publications
2
60
2
Order By: Relevance
“…Scanning electron microscopic examinations showed that the corrosion characteristics of the starch granules by amylase in the equid foregut were typical for grains. Endocorrosion through pin holes was observed in granules of corn, whereas on oats exocorrosion all around the surface was noted, while barley starch granules presented sporadic pin holes and small round structures on the surface (Kienzle et al, 1997).…”
Section: Enzymatic Activitymentioning
confidence: 92%
See 3 more Smart Citations
“…Scanning electron microscopic examinations showed that the corrosion characteristics of the starch granules by amylase in the equid foregut were typical for grains. Endocorrosion through pin holes was observed in granules of corn, whereas on oats exocorrosion all around the surface was noted, while barley starch granules presented sporadic pin holes and small round structures on the surface (Kienzle et al, 1997).…”
Section: Enzymatic Activitymentioning
confidence: 92%
“…Kleffken in 1993 (cited by Kienzle et al, 1997) postulated that the soluble starch, liberated by extruded corn, could flow with the liquid phase and thus have a shorter MRT than the insoluble form. These observations emphasized the major role that processing can have on the transit of digesta.…”
Section: The Effect Of Processing On the Prececal Digestion Of Starchmentioning
confidence: 99%
See 2 more Smart Citations
“…Starches and sugars in processed (flaked, rolled, steamed or popped) grains are more rapidly and efficiently digested than in whole, unprocessed grains (Hoekstra et al, 1999;Julliand et al, 2006, NRC, 2007, Keinzle et al 1997 though the overall benefits may be negligible to the actual biology of the horse, conferring only a 10% increase or less in most cases. Oat starch is more digestible than corn starch (Kienzle et al, 1997, NRC, 2007 which may account for the general perception that oats are safer than corn to feed in large amounts. If fed in large amounts to horses unaccustomed to the feed, cornstarch will be more likely to bypass digestion and absorption than oat starch, and be delivered in large amounts to the cecum and large colon where the resultant disruption of normal fermentation can result in altered digestion and even colic and laminitis (DeFombelle et al, 2004, Julliand et al, 2001Medina at al, 2002;Meyer et al, 1993;Moore and Dehority, 1993).…”
Section: Feed Types and Processingmentioning
confidence: 99%